Melioidosis parotitis in children. Issue 1 (December 2016) - Dance, David
Abstract A recent paper published inJVATiTD reporting a child in Hainan with parotitis caused byBurkholderia pseudomallei misleadingly described parotitis as a rare manifestation of melioidosis. In fact, it is one of the commonest forms of paediatric melioidosis seen in other parts of Southeast Asia, although interestingly not in Australia.